2019
DOI: 10.3390/app9224787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasonic Impact Treatment on the Stress-Controlled Fatigue Performance of Additively Manufactured DMLS Ti-6Al-4V Alloy

Abstract: Additive manufacturing (AM) offers many advantages for the mechanical design of metal components. However, the benefits of AM are offset to a certain extent by the poor surface finish and high residual stresses resulting from the printing process, which consequently compromise the mechanical properties of the parts, particularly their fatigue performance. Ultrasonic impact treatment (UIT) is a surface modification process which is often used to increase the fatigue life of welds in ship hulls and steel bridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A more recent trend in the hybrid AM field is the application of peening processes during the intermediate build phases. Surface modification processes such as peening [for example, shot peening (SP), hammer peening (HP), laser shock peening (LSP)] have been applied as a post processing step for AM components (Hönnige et al , 2017; Hackel et al , 2018; Maamoun et al , 2018; Walker et al , 2019; Xing et al , 2019; Gatto et al , 2020; Jin et al , 2020; Soyama and Takeo, 2020; Lesyk et al , 2021; Walczak and Szala, 2021; Aguado-Montero et al , 2022). More recently, they have been hybridized with AM processes such that they are applied to intermediate build layers (Gale and Achuhan, 2017; Kalentics et al , 2017a, 2017b, 2018, 2019, 2020; Sealy et al , 2021; Zhang et al , 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent trend in the hybrid AM field is the application of peening processes during the intermediate build phases. Surface modification processes such as peening [for example, shot peening (SP), hammer peening (HP), laser shock peening (LSP)] have been applied as a post processing step for AM components (Hönnige et al , 2017; Hackel et al , 2018; Maamoun et al , 2018; Walker et al , 2019; Xing et al , 2019; Gatto et al , 2020; Jin et al , 2020; Soyama and Takeo, 2020; Lesyk et al , 2021; Walczak and Szala, 2021; Aguado-Montero et al , 2022). More recently, they have been hybridized with AM processes such that they are applied to intermediate build layers (Gale and Achuhan, 2017; Kalentics et al , 2017a, 2017b, 2018, 2019, 2020; Sealy et al , 2021; Zhang et al , 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the disadvantage of ultrasonic nanocrystal surface modification is that it is not applicable to complex geometries. The experiments conducted by [24] showed that the ultrasonic impact treatment distributes residual stresses and generates a hardened surface. Additionally, it is able to close surface porosity and reduce roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of strain-induced phase transformations on the mechanical behavior of the highly stable Ti-6Al-4V alloy is also negligible. UIT provides benefits only for weld joints of Ti-6Al-4V, since it induces compressive stress improving their fatigue properties [5][6][7]. Moreover, the combination of UIT and Wire Arc Additive Manufacturing (WAAM) was recently proposed to improve the mechanical properties of Ti-6Al-4V parts [8].…”
Section: Introductionmentioning
confidence: 99%
“…The interstitials affect the electron structure of titanium causing its lattice transformation. However, the microstructural investigations of titanium alloys subjected to UIT are often focused on the evolution of dislocation density and grain structure [6,7], although the study of the strain-induced phase transformations should also yield both theoretical insight and practical results.…”
Section: Introductionmentioning
confidence: 99%